Comparison of Hemoglobin Levels in Mothers Before and After Cesarean Section at Bendan Hospital, Pekalongan City - Oktafiani, Aisah Fani; Wibowo, Subur (INDOGENIUS, 2025)
Background & Objective: Cesarean section, or Sectio Caesarea, is a frequently used delivery method when vaginal birth is not possible or poses a risk to the mother and baby. Method: The type of research conducted was comparative research, which aims to compare the hemoglobin levels in pregnant women before and after undergoing a cesarean section at Bendan Hospital. Hemoglobin level is a very important indicator for assessing maternal health status, particularly during and after the delivery process. Result: The average hemoglobin level before cesarean delivery was known to be 11.7 g/dl, with a minimum level of 9.1 g/dl and a maximum level of 14.8 g/dl. Furthermore, the average hemoglobin level in pregnant women after cesarean delivery was 10.8 g/dl, with a minimum level of 7.7 g/dl and a maximum level of 13.2 g/dl. Conclusion: Based on the parametric test (paired test), a sig value of 0.000 < 0.05 was obtained, meaning there is a statistically significant difference between the hemoglobin levels in pregnant women before and after delivering by cesarean section at Bendan Hospital.